Kajian Struktur dan Representasi Nilai Budaya dalam Novel Amba Karya Laksmi Pamuntjak - Maspuroh, Uah; Pratiwi, Wienike Dinar (Universitas Mathla'ul Anwar Banten, 2019)
This study aims to describe 1) the structure of the Amba novel by Laksmi Pamuntjak; 2) representation of cultural values ​​in Laksmi Pamuntjak's Amba novel. The object of this research is the Amba novel by Laksmi Pamuntjak. Through the qualitative research paradigm, this research was conducted using descriptive analysis methods and objective (structural) approaches based on the object of literary work itself. Novels are analyzed using several literary theories (1) structure theory according to Robert Stanton, Greimas structural theory to analyze the flow. (2) cultural value theory according to Kluckhohn. Representation of cultural values ​​in Amba's novel refers to five basic problems in life that determine cultural values ​​in accordance with what Kluckhohn has stated that each cultural value system contains five basic human problems. The five basic problems in human life that form the basis of the framework of the cultural value system are 1) the problem of the nature of human life; 2) the problem of the nature of human work; 3) the problem of the nature of human position in space and time; 4) the problem of the nature of human relations with the surrounding environment; and 5) the problem of the nature of human relations with each other.